2022
DOI: 10.7759/cureus.25378
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of COVID 19 Pneumonia in Vaccinated vs. Non-vaccinated Patients in the Second Wave: An Experience From a Tertiary Care Center in India

Abstract: Background: Coronavirus disease 2019 (COVID-19) is a novel infectious disease caused by SARS CoV-2 that emerged in Wuhan, China, and has rapidly spread worldwide. The mortality rate of critically ill COVID-19 patients is high. Objective: To assess the severity, different clinical symptoms, and comorbidities of COVID-19 pneumonia in vaccinated vs. non-vaccinated patients. Methods: In this single-center, cross-sectional study, 142 patients with COVID-19 were enrolled. The clinical character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In this study, we describe frequency, duration, and concentration of SARS-CoV-2, PMMoV, and mtDNA shedding in fecal specimens from inpatient and outpatient study subjects with COVID-19 over a 42 day period after the confirmation of SARS-CoV-2 infection. Consistent with other reports (2426), study subjects who had been vaccinated but had breakthrough infections were less likely to exhibit some clinical symptoms, such as cough, diarrhea, fever, loss of smell, loss of taste, and shortness of breath, compared to unvaccinated study subjects. Inpatient participants were more likely to be shedding SARS-CoV-2 RNA in their fecal specimens and had higher concentrations of the virus in their stool compared to outpatient participants.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we describe frequency, duration, and concentration of SARS-CoV-2, PMMoV, and mtDNA shedding in fecal specimens from inpatient and outpatient study subjects with COVID-19 over a 42 day period after the confirmation of SARS-CoV-2 infection. Consistent with other reports (2426), study subjects who had been vaccinated but had breakthrough infections were less likely to exhibit some clinical symptoms, such as cough, diarrhea, fever, loss of smell, loss of taste, and shortness of breath, compared to unvaccinated study subjects. Inpatient participants were more likely to be shedding SARS-CoV-2 RNA in their fecal specimens and had higher concentrations of the virus in their stool compared to outpatient participants.…”
Section: Discussionsupporting
confidence: 90%
“…In a previous study, comparison of symptomatology between vaccinated and unvaccinated cohorts in hospitalised patients showed more severe symptoms in unvaccinated [20]. The first community based COVID-19 vaccine studies in Israel showed that majority of vaccinated population were asymptomatic and needed less hospitalisation [21].…”
Section: Resultsmentioning
confidence: 90%
“…Bajpai et al found 43.7% were aged above 60 years, 26% of the vaccinated group experienced severe illness compared to 71.5% in the unvaccinated group. The allcause 30-day mortality in the non-vaccinated population was higher than that in the vaccinated population 16 Singh et al showed that the severity of the disease was 30.3%, 51.3%, 54.1% among fully, partially vaccinated and unvaccinated individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies were available on the incidence of COVID-19 infection after vaccination among general population. 8 Therefore, it was essential to analyse the severity of the disease and patient outcomes among the vaccinated and unvaccinated patients. Most of the COVID-19 suspect cases during the third wave were referred to this tertiary care COVID-19 hospital in Raigad District.…”
mentioning
confidence: 99%